2023
DOI: 10.1002/adsc.202300781
|View full text |Cite
|
Sign up to set email alerts
|

Hydroaminoalkyl Functionalization of Pyrimidin‐2(1H)‐ones by Visible Light Organophotocatalysis: A Radical Approach to Biginelli‐Type Dihydropyrimidines

Oleh Lukianov,
Viktor Tkachuk,
Svitlana Shishkina
et al.

Abstract: Herein, we report a visible‐light‐mediated hydroaminoalkylation of pyrimidin‐2(1H)‐ones via the aza‐Giese‐type reaction in presence of acridinium dye as photocatalyst under mild aerobic conditions. Using N‐Boc protected aminoalkyl trifluoroborates as radical precursors and various pyrimidine‐2(1H)‐one substrates, a diverse set of Biginelli‐type 3,4‐dihydropyrimidin‐2(1H)‐ones was prepared in 31–73% yields. Further transformation of the products obtained enabled the synthesis of 3,6,7,7a‐tetrahydro‐1H‐pyrrolo[3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The second approach (Scheme 1, B) was based on the visible-light-mediated hydroaminoalkylation of pyrimidin-2(1H)-ones 2a,b by the aza-Giese-type reaction with potassium N-Boc-aminomethyltrifluoroborate in the presence of an acridinium dye as a photocatalyst [9]. Further transformation of the radical addition products 5a,b enabled the synthesis of amine hydrochlorides 4a,b and, eventually, 3,6,7,7a-tetrahydro-1H-pyrrolo [3,4-d]pyrimidine-2,5-dione derivatives 1a,b, which showed promise as inhibitors of poly-(ADP-ribose) polymerase (PARP) enzymes (IC 50 0.46 -1.12 µM for PARP-2 in a fluorometric assay).…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The second approach (Scheme 1, B) was based on the visible-light-mediated hydroaminoalkylation of pyrimidin-2(1H)-ones 2a,b by the aza-Giese-type reaction with potassium N-Boc-aminomethyltrifluoroborate in the presence of an acridinium dye as a photocatalyst [9]. Further transformation of the radical addition products 5a,b enabled the synthesis of amine hydrochlorides 4a,b and, eventually, 3,6,7,7a-tetrahydro-1H-pyrrolo [3,4-d]pyrimidine-2,5-dione derivatives 1a,b, which showed promise as inhibitors of poly-(ADP-ribose) polymerase (PARP) enzymes (IC 50 0.46 -1.12 µM for PARP-2 in a fluorometric assay).…”
Section: Synthesismentioning
confidence: 99%
“…Recently, we have reported that the 4-trifluoromethyl-substituted 3,6,7,7a-tetrahydro-1H-pyrrolo [3,4-d]pyrimidine-2,5-dione core may serve as a scaffold for designing a novel class of PARP inhibitors, due primarily to the presence of the endocyclic amide fragment in the pyrrolidone ring, which resembles a key structural motif of the majority of PARP's nicotinamide site ligands [9]. This suggestion was supported by a molecular docking study, which additionally revealed that the trifluoromethyl group in position 4 of the novel scaffold may significantly contribute to the binding with the PARP enzyme NAD+ binding site due to the C•••F orthogonal dipolar interaction with the backbone peptide fragment.…”
Section: ■ Introductionmentioning
confidence: 99%